2015
DOI: 10.4018/978-1-4666-8363-1.ch016
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Challenges in Implementing Distance Learning and e-Learning

Abstract: In Tanzania, the growing demand for education due to massive enrolment in universities calls for adoption of Distance Learning (DL) and e-learning. Other factors for adoption include limited space and pace of learning, pedagogical weaknesses, and shortage of teaching staff. Mzumbe University also experiences the same as it operates satellite teaching centres of Morogoro town, Mbeya, Dar es Salaam, Tanga and Mwanza. This has made the university consider shifting from conventional delivery modes to alternative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The change to online platforms was not received positively by some students; for example, students from the University of Johannesburg (UJ) via the interim SRC were on social media calling for the institution to suspend online classes (Call to Suspend Online Learning at UJ, 2020). Reasons were described as characteristics related to technological, contextual and individualistic aspects (Sesabo et al, 2015). Individual characteristics, such as a lack of ICT training of teachers and students hinders the adoption of e-learning as a teaching and learning tool (Chisango, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The change to online platforms was not received positively by some students; for example, students from the University of Johannesburg (UJ) via the interim SRC were on social media calling for the institution to suspend online classes (Call to Suspend Online Learning at UJ, 2020). Reasons were described as characteristics related to technological, contextual and individualistic aspects (Sesabo et al, 2015). Individual characteristics, such as a lack of ICT training of teachers and students hinders the adoption of e-learning as a teaching and learning tool (Chisango, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Collaborating with others across the globe, producing academic work and communicating new knowledge are some of the requirements at the workplace (Steyn and van Greunen 2014). Information and communication technologies such as the internet provide opportunities for the marginalised and disadvantaged students who are not able to attend classes (Sesabo et al 2015;Shraim and Khalif 2010). Internet allows easy transmission of information, creating global networks and economic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Recent results of standardized tests like PISA reveal structural quality issues that have been becoming evident in recent years and have triggered various educational initiatives, especially through the incorporation of ICT (SESABO et al, 2015). Examples like blended and flipped learning, m-learning, and recently the Massive Open Online Courses (MOOC) have shown that it is possible to generate educational change if educational practices are modified going beyond setting or updating content (LEVENE; SEABURY, 2014;RAYYAN et al, 2016;STYLIANIDIS, 2015).…”
Section: Introductionmentioning
confidence: 99%